Discrete-event computer simulation methods in the optimisation of a physiotherapy clinic. - Villamizar J; Coelli F; Pereira W; Almeida R (Physiotherapy, 2011)
Abstract: Objective: To develop a computer model to analyse the performance of a standard physiotherapy clinic in the city of Rio de Janeiro, Brazil. Design and setting: The clinic receives an average of 80 patients/day and offers 10 treatment modalities. Details of patient procedures and treatment routines were obtained from direct interviews with clinic staff. Additional data (e.g. arrival time, treatment duration, length of stay) were obtained for 2000 patients from the clinic''s computerised records from November 2005 to February 2006. Methods and main outcome measures: A discrete-event model was used to simulate the clinic''s operational routine. The initial model was built to reproduce the actual configuration of the clinic, and five simulation strategies were subsequently implemented, representing changes in the number of patients, human resources of the clinic and the scheduling of patient arrivals. Results: Findings indicated that the actual clinic configuration could accept up to 89 patients/day, with an average length of stay of 119minutes and an average patient waiting time of 3minutes. When the scheduling of patient arrivals was increased to an interval of 6.5minutes, maximum attendance increased to 114 patients/day. For the actual clinic configuration, optimal staffing consisted of three physiotherapists and 12 students. According to the simulation, the same 89 patients could be attended when the infrastructure was decreased to five kinesiotherapy rooms, two cardiotherapy rooms and three global postural reeducation rooms. Conclusions: The model was able to evaluate the capacity of the actual clinic configuration, and additional simulation strategies indicated how the operation of the clinic depended on the main study variables.